2008
DOI: 10.1063/1.2898221
|View full text |Cite
|
Sign up to set email alerts
|

Efficient light coupling from integrated single-mode waveguides to supercollimating photonic crystals on silicon-on-insulator platforms

Abstract: We propose a practical and efficient solution for the coupling of light from integrated single-mode waveguides to supercollimating planar photonic crystals on conventional silicon-on-insulator platforms. The device consists of a rib waveguide, designed to sustain spatially extended single-modes and matched to a supercollimating photonic crystal, which has been truncated at its boundary to improve impedance matching between the two photonic components. Three-dimensional simulations show transmission efficiencie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Now, we examine the transport behaviors of energy fluxes in a transmission line composed of different types of edges, so as to explore and demonstrate how PCTIs can overcome the mode-mixing problems and impedance-mismatching issues at the terminals. In general, two simple but very useful parameters, the reflection coefficient r n,n +1 = ( Z n +1 − Z n )/( Z n +1 + Z n ) and transmission coefficient t n , n +1 = 2 Z n +1 /( Z n +1 + Z n ), can be used to characterize the degree of impedance mismatching [ 7 , 8 , 9 ]. As shown in Figure 3 , for the n th interface, Z n and Z n +1 are the wave impedances for the input n th PhC waveguide and the output ( n + 1)th PhC waveguide, respectively.…”
Section: Topological Resistance-free One-way Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, we examine the transport behaviors of energy fluxes in a transmission line composed of different types of edges, so as to explore and demonstrate how PCTIs can overcome the mode-mixing problems and impedance-mismatching issues at the terminals. In general, two simple but very useful parameters, the reflection coefficient r n,n +1 = ( Z n +1 − Z n )/( Z n +1 + Z n ) and transmission coefficient t n , n +1 = 2 Z n +1 /( Z n +1 + Z n ), can be used to characterize the degree of impedance mismatching [ 7 , 8 , 9 ]. As shown in Figure 3 , for the n th interface, Z n and Z n +1 are the wave impedances for the input n th PhC waveguide and the output ( n + 1)th PhC waveguide, respectively.…”
Section: Topological Resistance-free One-way Transportmentioning
confidence: 99%
“…This surely is an important problem that cannot be neglected in the design of practical PhCs-based optical devices. Hence, reducing or avoiding mode-mixing problems at intersections and impedance-mismatching issues at discontinuities becomes a crucial issue that must be taken into full account in improving the transport efficiency of PhCs-based circuits and devices [ 7 , 8 , 9 ]. If one does not have to deal with such mode-mixing problems and impedance-mismatching issues, the design of PhCs-based optical devices will become much simplified.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the reflection losses, the interfaces of PhC slabs are modified to increase the coupling efficiencies. In the present work, we conduct numerical simulations for two cases: PhC slabs with adiabatic matching array (AMA) interfaces, also called graded PhCs [25], and PhC slabs with truncation of the first-column interface (TFC interfaces) [17]. After numerical comparisons, it was found that the latter are a better choice for increasing transmission efficiencies of light.…”
Section: The Dependence Of the Interface: The Adiabatic Matching Arra...mentioning
confidence: 99%
“…Besides, it is worthy of note that coupling losses when light is incident into PhC slabs are still expected to be reduced. It is known that the coupling losses will lead to reductions of the available coupling angles and coupling efficiencies [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…4 were smoothed to take out the high-order Fabry-Perot fringes arising from the cavities delimited between the facet of waveguides IN1, OUT1, OUT2 and the waveguide/PhC interfaces [20] and the low-order Fabry-Perot fringes, mainly arising from the shorter cavities delimited between the waveguide/PhC interfaces. These fringes can be suppressed by improving the mode-matching between waveguide and PhC, for example by using rib waveguides instead of ridge waveguides [21], or by entering the light into the PhC with a free-space beam and using an antireflection coating structure [22]. In future work, we will include mode-matching structures in order to improve the optical performance of the PhC MZI.…”
Section: Transmission Measurementmentioning
confidence: 99%